Have Pandemic Measures Reduced the Frequency of Febrile Seizures? Assessment of the Frequency of Febrile Seizures in the Pre- and Post-COVID-19 Period - Nazlı Sivil; Furkan Donbaloğlu; Özlem Tolu Kendir; Nilgün Erkek; Özgür Duman; Şenay Haspolat (Güncel Pediatri)
Introduction: Febrile seizures (FS) are common childhood seizures often triggered by fever. With the emergence of coronavirus disease 2019 (COVID-19), FS cases related to the COVID-19 have also been reported. This study aimed to assess the effect of COVID-19 preventive measures on frequency with FS to the pediatric emergency department and compare characteristics of FS patients between the pre-pandemic and pandemic periods. Materials and Methods: A retrospective, descriptive study was conducted using data from the our hospital’s pediatric emergency service between March 11th, 2018, and March 10th, 2022. Patients aged between 6 to 60 months with FS were included in to the study. Results: A total of 385 FS admissions from 342 patients were evaluated. During the pandemic period, total paediatric emergency admissions decreased by 38.3%, while admissions related to FS decreased by 51.4%. The ratio of FS-related admissions to total admissions decreased from 0.30% to 0.23% (p=0.025). The distribution of FS type differed significantly between the pre-pandemic and pandemic periods (p=0.006), and the proportion of complicated FS cases was higher during the pandemic. Conclusions: This study revealed a decline in FS admissions during the COVID-19 pandemic, most likely due to quarantine measures that reduced the transmission of respiratory infections. Notably, the rate of admission of complex FS cases and hospitalizations increased during the pandemic. Adherence to isolation and hygiene practices might contribute to reducing FS incidence in the aftermath of the pandemic.